Atividade imunomoduladora de IFN-y e IL-17 sobre a função eritrofagocítica de Entamoeba histolytica - Silva, Kelen Monik Gomes da (2016)
Entamoeba histolytica is the causative protozoan of amebiasis. This disease is the second leading cause of death worldwide among the parasitic diseases and presents the intestinal forms and extra-intestinal. Trophozoites, invasive form of amoeba have erythrophagocytic capacity, the capacity to phagocytic of erythrocytes. The functional activity of cytokines in phagocytosis has been reported in blood cells and colostrum, but in the process of phagocytosis of this parasite has not been elucidated. Therefore, to identify cytokines which may modulate the action of phagocytic trophozoites in erythrophagocytosis, it is necessary for a better understanding of immune responses during amebiasis.The objective of this work was to evaluate the immunomodulatory effects of IFN-γ and / or IL-17 on erythrophagocytosis of E. histolytica. The methods used were red cell viability assay and erythrophagocytosis assay and a total of 18 samples of human peripheral blood from volunteer donors. Statistical analysis was performed by analysis of variance (ANOVA) followed by Tukey method. There was an increase of erythrophagocytosis and variation in the number of phagocytic amoeba and phagocytosed erythrocytes in accordance with the cytokine.The amoebae phagocytic index was higher when cells were treated with cytokines. The highest value was observed in the assay containing IFN-γ followed by IFN-γ + IL-17 and IL-17. IFN-γ and the combination of IFN-γ + IL-17 increased the number of phagocytosed erythrocytes.The results suggest that cytokines play a role in the pathogenesis of amebiasis, amoeba by interfering with the interaction with erythrocytes increase the erythrophagocytosis, the procedure as virulence factor of pathogenic amoebae strains.